Projecting Ancient Ancestry in Modern-Day Arabians and Iranians: A Key Role of the Past Exposed Arabo-Persian Gulf on Human Migrations. (4th September 2021) - Ferreira, Joana C; Alshamali, Farida; Montinaro, Francesco; Cavadas, Bruno; Torroni, Antonio; Pereira, Luisa; Raveane, Alessandro; Fernandes, Veronica
Abstract: The Arabian Peninsula is strategic for investigations centered on the early structuring of modern humans in the wake of the out-of-Africa migration. Despite its poor climatic conditions for the recovery of ancient human DNA evidence, the availability of both genomic data from neighboring ancient specimens and informative statistical tools allow modeling the ancestry of local modern populations. We applied this approach to a data set of 741, 000 variants screened in 291 Arabians and 78 Iranians, and obtained insightful evidence. The west-east axis was a strong forcer of population structure in the Peninsula, and, more importantly, there were clear continuums throughout time linking western Arabia with the Levant, and eastern Arabia with Iran and the Caucasus. Eastern Arabians also displayed the highest levels of the basal Eurasian lineage of all tested modern-day populations, a signal that was maintained even after correcting for a possible bias due to a recent sub-Saharan African input in their genomes. Not surprisingly, eastern Arabians were also the ones with highest similarity with Iberomaurusians, who were, so far, the best proxy for the basal Eurasians amongst the known ancient specimens. The basal Eurasian lineage is the signature of ancient non-Africans who diverged from the common European-eastern Asian pool before 50, 000 years ago, prior to the later interbred with Neanderthals. Our results appear to indicate that the exposed basin of the Arabo-Persian Gulf was the possible home of basal Eurasians, a scenario to be further investigated by searching ancient Arabian human specimens.